Does China’s iron ore futures market have price discovery function? Analysis based on VECM and State-space perspective - Ge, Yongbo; Cao, Tingting; Jiang, Ruchuan; Liu, Peide; Xie, Hengxin (Journal of Business Economics and Management, 2019)
As the world’s largest importer, trading of iron ore occupies a pivotal position in China’s international trade. In order to seek the decision power of deciding the price for iron ore, China’s Dalian Commodity Exchange (DCE) listed iron ore futures in October 2013,which has become the world’s largest iron ore financial derivatives trading market now. Based on VECM and state-space perspective, this paper aims to explore the price discovery function of iron ore futures on the DCE. Comprehensive analysis from the views of long-term equilibrium relationship, short-term information shocks and dynamic contribution share are made in this paper. The empirical results show that: firstly, from the perspective of cointegration test, there is a long-term equilibrium relationship between the futures prices in DCE and the spot prices; secondly, when facing with short-term information shocks, iron ore futures in DCE have an obviously price discovery function by the analysis of impulse response and variance decomposition; finally, by the way of state-space and Kalman filter algorithm, the long-term equilibrium relationship dynamic contribution for price discovery function of DCE’s iron ore futures remains stable between 60% and 70% now.